PERBEDAAN PERSEPSI ETIS MAHASISWA AKUNTANSI TERHADAP PRAKTIK EARNINGS MANAGEMENT (Studi Kasus pada Universitas Diponegoro) - Nurul Khanifah; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2020)
This research aims to find out whether there is a perception difference in Diponegoro University students toward earnings management practice based on 5th and 7th term and based on gender. The method for gathering data is questionnaires, in which data is gathered by  a  series  of  written  questions  answered  by  participants.  Students  asked  for  response samples are those who have learned Business Ethics, Cost Accounting, Management Accounting, Auditing 1,  Auditing 2 and Theory Accounting. The total of participants are 100 Accounting students. Two-Way ANOVA is used as an analytical device.The  results  are  as  follows:  1.)  First  test  results  shows  that  there  is  significant perception difference in students who have learned Business Ethics, Cost Accounting, Management Accounting, Auditing 1, Auditing 2 and Theory Accounting. 2.) Second test result shows that there is significant difference between male and female students.